Pengaruh Kompetensi Sumber Daya Manusia Terhadap Kinerja Pegawai Bank Sumut Cabang Lahewa - Zega, Yamolala; Baene, Eduar; Mendrofa, Martha Surya Dinata (Jurnal Sains dan Teknologi, 2023)
This study discusses how the influence of Human Resource Competence on the Performance of Bank Sumut Lahewa Branch Employees. This study aims to determine how human resource competence affects and how much influence it has on the performance of employees of the Bank Sumut Lahewa Branch. This study used an inference data analysis approach method, with a saturated sample of 32 people which made all employee populations at Bank Sumut Lahewa Branch into samples in this study. The data collection technique in this study was using questionnaire dissemination techniques. This research uses analysis techniques of Data Verification, Hypothesis Test (t-Test and F Test), Coefficient of Determination, and Correlation Coefficient. And Linear Regression analysis is simple. Data processing in this study uses the Product Moment Correlation formula. The results of this study show that partially the competence of Human Resources has a positive and significant effect on the Performance of Bank Sumut Lahewa Branch Employees. It is simultaneously observed that Human Data Source Competence has a significant positive influence on the Performance of Bank Sumut Lahewa Branch Employees.